Preparation of 2D Molybdenum Phosphide via Surface‐Confined Atomic Substitution. Issue 35 (28th July 2022) - Wang, Wenbin; Qi, Junlei; Zhai, Li; Ma, Chen; Ke, Chengxuan; Zhai, Wei; Wu, Zongxiao; Bao, Kai; Yao, Yao; Li, Siyuan; Chen, Bo; Repaka, D. V. Maheswar; et al.
Abstract: The emerging nonlayered 2D materials (NL2DMs) are sparking immense interest due to their fascinating physicochemical properties and enhanced performance in many applications. NL2DMs are particularly favored in catalytic applications owing to the extremely large surface area and low‐coordinated surface atoms. However, the synthesis of NL2DMs is complex because their crystals are held together by strong isotropic covalent bonds. Here, nonlayered molybdenum phosphide (MoP) with well‐defined 2D morphology is synthesized from layered molybdenum dichalcogenides via surface‐confined atomic substitution. During the synthesis, the molybdenum dichalcogenide nanosheet functions as the host matrix where each layer of Mo maintains their hexagonal arrangement and forms isotropic covalent bonds with P that substitutes S, resulting in the conversion from layered van der Waals material to a covalently bonded NL2DM. The MoP nanosheets converted from few‐layer MoS2 are single crystalline, while those converted from monolayers are amorphous. The converted MoP demonstrates metallic charge transport and desirable performance in the electrocatalytic hydrogen evolution reaction (HER). More importantly, in contrast to MoS2, which shows edge‐dominated HER performance, the edge and basal plane of MoP deliver similar HER performance, which is correlated with theoretical calculations. This work provides a new synthetic strategy for high‐quality nonlayered materials with well‐defined 2D morphology for future exploration. Abstract : Nonlayered molybdenum phosphide (MoP) with well‐defined 2D morphology and tunable crystallinity can be prepared from layered molybdenum dichalcogenides via surface‐confined atomic substitution. In contrast to the well‐documented edge‐dominated electrocatalytic performance of the MoS2 precusor, the entire basal plane of MoP demonstrates satisfying electrocatalytic hydrogen evolution reaction performance owing to its coordination‐unsaturated surface atoms with abundant dangling bonds.